STRUKTUR MODAL MEMODERASI HUBUNGAN KOMITE AUDIT DAN INVESTMENT OPPORTUNITY SET DENGAN KUALITAS LABA - Heni Yati; Holiawati Holiawati; Enang Ruhiyat (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to examine the effect of the audit committee, investment opportunity set on earnings quality with capital structure as a moderating variable. This type of research is associative quantitative. This research was conducted using secondary data in the form of company financial reports. This study uses a population of Basic Materials Sector Companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021 through its official website www.idx.co.id. Based on purposive sampling, the samples obtained were 29 companies from 95 basic materials companies listed on the Indonesia Stock Exchange in 2017-2021 so that the total sample during the study period was 145 companies. Data processing analysis techniques use the help of the eviews ver-12 application. The data analysis used in this research is panel data regression analysis. Based on the statistical results that have been carried out, it shows that the audit committee has no effect on earnings quality, the investment opportunity set has a negative effect on earnings quality, capital structure cannot moderate the relationship between audit committees and earnings quality and capital structure cannot moderate the investment opportunity set relationship with earnings quality.